2003
DOI: 10.5081/jgps.2.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Kalman Filtering for Vehicle Navigation

Abstract: Abstract. Kalman filters have been widely used for navigation and system integration. One of the key problems associated with Kalman filters is how to assign suitable statistical properties to both the dynamic and the observational models. For GPS navigation, the manoeuvre of the vehicle and the level of measurement noise are environmental dependent, and hardly to be predicted. Therefore to assign constant noise levels for such applications is not realistic.In this paper, real-time adaptive algorithms are appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(81 citation statements)
references
References 5 publications
0
79
0
2
Order By: Relevance
“…For actual MMR systems, this is difficult to satisfy because of the vast workload. It is well known that the adaptive filter can be utilized to estimate and correct the model parameters and the noise characteristics at the same time [20]. As a result, the adaptive filter has been considered to enhance the estimation accuracy in robotics [21,22].…”
Section: Problem Statementsmentioning
confidence: 99%
“…For actual MMR systems, this is difficult to satisfy because of the vast workload. It is well known that the adaptive filter can be utilized to estimate and correct the model parameters and the noise characteristics at the same time [20]. As a result, the adaptive filter has been considered to enhance the estimation accuracy in robotics [21,22].…”
Section: Problem Statementsmentioning
confidence: 99%
“…It was found that four-level wavelet transform was best suited for this study where first two PC covered more than 99% of information variation [14]. Individual stage of decomposition process provided detailed j+1 coefficients where as j th coefficient after the final stage of wavelet was eventually used as representative feature of that class or month in this case [14][15][16][17]. …”
Section: Discrete Wavelet Transform: Feature Extractionmentioning
confidence: 99%
“…Loebis et al (Loebis et al, 2004) proposed an adaptive EKF algorithm, which adjusted the measurement noise covariance matrix by fuzzy logic. Other works can also be seen in references (Noriega & Pasupathy, 1997;Mehra, 1970;Hu et al, 2003;Chaer et al, 1997;Garcia-Velo, 1997). As far as the adaptive UKF (AUKF) is concerned, the most-oftenmentioned scheme was proposed by Lee and Alfriend (Lee & Alfriend, 2004), where the Maybeck's method (Maybeck, 1979) was modified by maximum-likelihood principle to estimate the error covariance matrix, and this estimator was further integrated into the normal UKF as the adaptive mechanism.…”
mentioning
confidence: 99%